Furosemid-tartalmú kúpok előállítása, in vitro vizsgálata és a preklinikai alkalmazás tapasztalatai - Regdon Géza; Fazekas Tamás; Regdon Géza (ifj.); Selmeczi Béla (1997)
Rectal suppositories containing Furosemide (4-Chloro-N-furfuryl-5-sulfamoylanthranilic acid) and Furosemide Sodium were formulated with various suppository bases. The in vitro drug release of Massa Estarinum 299 proved to be the best from among the vehicles having various physical-chemical properties. The diuretic effect of the two suppositories was compared in a prospective, cross-over clinical trial including 8 patients. Both preparations have induced and increase of urine flow, which was comparable to the diuretic effect of the tablet. Thus the possibility of rectal use has been added to the modalities of therapeutic Furosemide administration.
Keywords: Általános orvostudomány; Klinikai orvostan; Egyéb orvostudományok